Gestão democrática participativa em comunidades de aprendizagem : a perspectiva de profissionais de uma escola pública da rede estadual de ensino em Rondonópolis - MT - Franco, Maurita César de Morais (2016)
This master’s thesis was developed within the Master Degree Program in Education of Federal University of Mato Grosso (PPGEdu/CUR/UFMT) in the line of research Teacher Education and Educational Public Policies. This research is entitled Democratic and Participative Management in Learning Communities: the perspective of professionals from a public school in Rondonópolis – MT and it aims to investigate the management of a state school which decided collectively to adopt the learning communities’ proposal to change students’ reality through successful educational actions. The research adopts an intersubjective approach to analyze the understanding and experiences of the professionals from this school attempting to understand how does the implementation process of the learning community’s proposal occur in the context of a democratic and participative school management context. This inquiry is based on a communicative methodology with an interpretative-qualitative approach. Communicative observation, in-depth interviews and communicative narratives were used as data collection instruments. The discussions were based on the educational theories and the sociological studies of Habermas (2002, 2004) and Freire (2011, 2012) about dialogicity and communicative action. The concept of dialogic learning created by the Centre of Research in Theories and Practices that Overcome Inequalities (CREA/ University of Barcelona – Spain) was used to analyze the data collected in 2014, 2015 and 2016. The use of dialogic theories enabled to structure the analysis according the communicative methodology steps and it evidenced transformers elements and exclusionary ones. Thus, the transformers elements pointed by the participants refer to the benefits of the construction of a democratic and participative management to the organization and operation of the school and to the operation of the educational system as well. The exclusionary elements mentioned by the participants were related to factors which complicate or impede the implementation of a democratic and participative management. They revealed the limitations perceived in the construction of the democratic process, its challenges and the possibilities of successful educational actions to the management and consolidation of the learning communities’ proposal. Considering the current school context, we argued that this master’s thesis theme isn’t depleted yet. Instead, it raises several questions to future investigations. Reflecting about this theme may contribute to create a humanized and democratic school environment, promoting a participative culture and building dialogic and transformer spaces based on inclusion principles and rights equality.